Modulation of thyroid hormone receptors, TRα and TRβ, by using different doses of triiodothyronine (T3) at different times - Miriane, Oliveira [UNESP]; Luvizoto, Renata de Azevedo Melo [UNESP]; Olimpio, Regiane Marques Castro [UNESP]; Síbio, Maria Teresa [UNESP]; Silva, Carolina Biz Rodrigues; Conde, Sandro José [UNESP]; Padovani, Carlos Roberto [UNESP]; Nogueira, Célia Regina [UNESP] (My University, 2013)
Objective: To examine the effect of different doses of triiodothyronine (T3) on mRNA levels of thyroid hormone receptors, TRα and TRβ, at different times. Materials and methods: 3T3-L1 adipocytes were incubated with T3 (physiological dose: F; supraphysiological doses: SI or SII), or without T3 (control, C) for 0.5, 1, 6, or 24h. TRα and TRβ mRNA was detected using real-time polymerase chain reaction. Results: F increased TRβ mRNA levels at 0.5h. After 1h, TRα levels increased with F and SI and TRβ levels decreased with SII compared with C, F, and SI. After 6h, both genes were suppressed at all concentrations. In 24h, TRα and TRβ levels were similar to those of C group. Conclusions: T3 action with F began at 1h for TRα and at 0.5h for TRβ. These results suggest the importance of knowing the times and doses that activate T3 receptors in adipocytes.

Objetivo: Examinar o efeito de diferentes doses de triiodotironina (T3) sobre a expressão gênica dos receptores TRα e TRβ em diferentes tempos. Materiais e métodos: Adipócitos, 3T3-L1, foram incubados com T3 nas doses fisiológica (F, 10nM) e suprafisiológicas (SI, 100nM ou SII, 1000nM) ou veículo (controle, C) durante 0,5, 1, 6 ou 24h. mRNA dos TRs foram detectados utilizando PCR em tempo real. Resultados: Níveis de TRβ aumentaram em F em 0,5h. Após 1h, níveis de TRα aumentaram em F e SI comparado ao C, enquanto TRβ diminuiu no SII comparado com C, F, e SI. Após 6h, ambos os genes foram suprimidos em todas concentrações. Em 24h, níveis de TRα e TRβ retornaram aos do C. Conclusões: Ação do T3 em F iniciou-se em 1h para TRα e 0,5h para TRβ. Esses resultados são importantes para determinar tempo inicial e dose de T3 em que os receptores de HT são ativados em adipócitos.
Modulação dos receptores de hormônio tireoidiano, TRα e TRβ, utilizando diferentes doses de triiodotironina (T3) em diferentes tempos
Keywords: TRα; TRβ; Triiodothyronine; Adipocytes; TRα; TRβ; Triiodotironina; Adipócitos